Analysis of Accounting Treatment for Biological Assets Based on Psak 241 and Its Implications for Sales Pricing Determination in Desa Mulya Farmers Group - Yanisa Citra Trilaxmi Nasution; Rahmat Daim Harahap; Budi Harianto (Jurnal Investasi Islam, 2026)
Agricultural financial governance at the grass-roots level often suffers from systemic distortions. Previous studies remain heavily dominated by large corporate plantations or intensive horticultural industries, presenting a severe contextual gap. Consequently, existing research is insufficient as it fails to bridge standard accounting treatments with downstream economic metrics, leaving a distinct theoretical and empirical gap where biological asset accounting is treated in isolation from market pricing and a farmer's bargaining power. This descriptive qualitative study addresses these deficiencies at the Desa Mulya Farmer Group in Deli Serdang Regency, North Sumatra. Data were gathered through concurrent field observations and in-depth interviews with two core management key informants. Technical triangulation was employed by cross-comparing interview transcripts, physical transformation observations, and calculated production data within the interactive model of data reduction, display, and conclusion drawing. The findings revealed a massive compliance gap across all four pillars of PSAK 241 (recognition, measurement, presentation, and disclosure) due to an output-oriented mindset that fails to capitalize vegetative asset transformations. However, the mathematically reconstructed production cost established a precise internal Cost of Production (HPP/HPP) baseline of IDR 2,304/kg. Comparing this against the middlemen's dictated price of IDR 6,500/kg yielded a highly profitable margin and an efficient R/C ratio of 2.8. This study provides a vital theoretical contribution by establishing a strategic chain proving that biological capitalization is mathematically essential to eliminate smallholder financial bias. Practically, it equips communal administrators with a structured cost accounting mechanism. Ultimately, the policy implication underscores that PSAK 241 functions as a strategic management control tool to shift rural producers from vulnerable price-taking dependencies into data-driven price-evaluators against dominant middlemen networks.